(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The author in suggested article analysis the representation of the Soviet past in contemporary Russian and Ukrainian novels. Nostalgia for the past, represented by the modern popular novel, is controversial. They define restorative and reflexive nostalgia (after S. Boym). We are talking about the appropriation of cultural memory and, to a lesser extent, the qualitative rethinking of history. The author of the article illustrates the main thesis of his work with the quotes of writings of the prominent Russian writers, such as Mikhail Elizarov, Andrey Turgeniev, Eduard Limonov, Aleksandr Prokhanov as well as Ukrainian ones – Yuriy Andrukhovych, Serhiy Zhadan, Oleksandr Irvanets etc.